Understanding the Psychosocial and Parenting Needs of Mothers with Irritable Bowel Syndrome with Young Children - Lexa K. Murphy; Tanera R. van Diggelen; Rona L. Levy; Tonya M. Palermo (Children, 2020)
Women of childbearing age experience the highest prevalence of irritable bowel syndrome (IBS), yet little is known about their psychosocial and parenting needs, which may influence their children’s experience of future gastrointestinal or pain-related conditions. The aims of this study were to conduct qualitative interviews to understand the psychosocial and parenting needs of mothers with IBS who have young school-age children, and to assess mothers’ potential interest in and acceptability of a preventive parenting intervention program. Ten mothers with IBS who have young (age 5–10), healthy children were interviewed. Interviews were coded with thematic analysis and three themes were identified: (1) Guilt about how IBS impacts children, (2) Worry that children will develop IBS, and (3) Already on high alert for children’s health. All mothers expressed interest in an Internet-based preventive intervention and identified tools and strategies they would want included. Results demonstrate that mothers experience guilt about how IBS has impacted their children in their daily lives, concern that they need to pay attention to children’s early signs and symptoms that could indicate gastrointestinal problems, and worry about children developing IBS in the future—suggesting that a preventive intervention may address important concerns for this population.